Diagnostic Value of Combined Detection of Serum TTR, PP13 and PLGF in Preeclampsia Patients - Ying Jiang; Caifeng Deng; Xuehua Cheng; Xiaofeng Chen (IMR Press, 2023)
Background: To investigate the diagnostic value of serum transthyretin (TTR), placental protein 13 (PP13) and placental growth factor (PLGF) in preeclampsia patients. Methods: Sixty cases of pregnant women with preeclampsia who were examined in our hospital from January 2020 to February 2022 were retrospectively selected as the preeclampsia group, and 40 cases of healthy pregnant women who received regular physical examination in our hospital during the same period were selected as the control group. Based on the severity of the disease, the patients were allocated into two groups: mild preeclampsia group (n = 35) and severe preeclampsia group (n = 25). The levels of Serum TTR, PP13 and PLGF were compared between the groups. The correlation between serum TTR, PP13, PLGF and the patients was also analyzed by Spearman method, and receiver operating characteristic curve (ROC) and area under the curve (AUC) was adopted to analyze the clinical value of the separate and combined detection of serum TTR, PP13, PLGF in the diagnosis of preeclampsia. Results: The levels of serum TTR, PP13, PLGF in preeclampsia group were evidently lower versus the control group (p < 0.05), and those of patients in mild preeclampsia group were markedly lower versus the control group (p < 0.05), while those in severe preeclampsia group were markedly lower versus the mild preeclampsia group and control group (p < 0.05). Serum TTR, PP13, PLGF levels in preeclampsia patients were negatively correlated with the disease progression (r = -0.332, -0.315, -0.391, p < 0.05). The AUC values of TTR, PP13, PLGF in the single diagnosis of preeclampsia and their joint diagnosis were 0.812, 0.759, 0.867, and 0.887, respectively. The area under the ROC curve of TTR, PP13, and PLGF joint diagnosis of preeclampsia was higher than that of PP13 alone (p < 0.05). Conclusions: Serum TTR, PP13, and PLGF levels of preeclampsia patients were decreased compared with those of the control group, and the decrease was more significant with the aggravation of the disease, suggesting that TTR, PP13, and PLGF could be used as indicators to predict the onset and severity of preeclampsia. The combination of the three indicators could improve the diagnostic efficiency.